Integration of Customary Criminal Law in the National Criminal Justice System Based on Pancasila and Progressive Law - Ayub Jose Luhut Parulian Simanjuntak; Abdul Malik Mufty; Nurul Chaerani Nur; Vivilia Agnata Mudi; Muhammad Khaidir Kahfi Natsir (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The integration of customary criminal law into Indonesia’s national criminal justice system reflects the constitutional recognition of legal pluralism as stipulated in Article 18B(2) of the 1945 Constitution and reinforced by Article 2 of Law No. 1 of 2023 on the Criminal Code. The dominance of a positivist legal paradigm, which emphasizes written law, has often marginalized living law and reduced the role of restorative justice practiced by indigenous communities. This study aims to analyze the normative position of customary criminal law within the national legal framework, identify conceptual and normative challenges in harmonizing state law and customary law, and formulate a contextual, equitable, and sustainable integration model. The research employs a normative legal approach using statutory, conceptual, and historical-philosophical methods. Data are derived from primary legal materials, secondary legal literature, and tertiary sources to support doctrinal analysis. The findings indicate that the recognition of customary criminal law in the 2023 Criminal Code represents significant progress toward legal pluralism. However, its implementation remains constrained by the absence of implementing regulations, differing interpretations, and the potential subordination of living law to state law. Therefore, integration should be guided by a progressive legal approach and Pancasila values to strengthen indigenous institutions, promote substantive justice, protect vulnerable groups, reduce the burden on formal courts, and support a more inclusive and responsive legal system.